Bleeding in renal failure: a possible cause. Issue 6036 (11th September 1976) - Kazatchkine, M; Sultan, Y; Caen, J P; Bariety, J
Abstract : Increased concentrations of factor VIII-related antigen (VIIIRA), factor VIII-procoagulant activity (VIIC), and decreased factor VII-von Willebrand activity (VIIIVWF) were found in the plasma of patients with chronic renal failure (CRF). This functional abnormality of the factor VII protein may partly explain the prolonged bleeding time commonly found in CRF. It was not improved by dialysis, but it was no longer found in patients with normally functioning grafted kidneys after the sixth month after transplantation. VIIIVWF levels remained decreased when compared with VIIIRA or VIIIC in transplanted patients undergoing acute reversible rejection soon after transplantation. Yet, not only VIIIC and VIIIRA but also VIIIVWF were greatly increased in patients with hyperacute irreversible rejection. Possibly a high VIIIVWF level in these patients is a thrombogenic factor.